EFEKTIFITAS IKLAN GO-JEK PENGGUNA MEDIA SOSIAL KOTA PADANG - Tri Irfa Indrayani; Asrizal Asrizal; Nurdiah Shalat (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract : Research Objectives to measure and analyze the effectiveness of Go-Jek online advertising on social media. This study uses a sample to residents who live in Padang City and are social media users. Sampling was done by Purpose sampling with 100 respondents. The data analysis technique used is the EPIC method, which consists of; empathy (empathy), persuasion (persuasion), impact (impact), and communication (communication). The EPIC analysis results partially for each variable are in the "effective" range because the average value of empathy = 3.9375, persuasion = 3.9273, impact = 3.8175, and communication = 3.92. And the EPIC rate which is the average value of the whole variable is at 3.9. This value is in the "effective" range on the effectiveness scale. This shows that Go-Jek online advertisements through social media are considered effective in attracting audience empathy, effective in influencing audience buying interest, effective in leaving a good impression on the audience, and effective in delivering messages clearly, well, and correctly. Keywords: Effectiveness, EPIC Method